Reaction to crisis in gothic romance - Braček, Tadej (ELOPE (Ljubljana), 2016)
Gothic romances were primarily women's domain. This is proven by the fact that from the end of the eighteenth century to the beginning of the nineteenth century more than fifty female authors wrote Gothic romances. In the first part the paper depicts the emergence of romances, clarifies the notion of the Gothic and explains the theory of Gothic romances. The second part focuses on Ann Radcliffe's first novel, The Castles of Athlin and Dunbayne. This section analyses in what way men and women react to crises. It concludes that reactions are primarily based not on sex but on the benevolence and malevolence of literary characters. The former react with higher intensity on the physical level (passing out, becoming ill) and the latter react vehemently in emotional sense towards their rivals. The originality of the article lies in the systematic analysis of characters' responses to crisis and in the study of atypical features of this Gothic novel.
Keywords: "The Castles of Athlin and Dunbayne"; angleška književnost; gotska romanca; literarne študije; man; moški; odzivi na krize; Radcliffe, Ann, 1764-1823; woman; ženske